Torsional balance as new design criterion for asymmetric structures with energy dissipation devices. - Almazán, José L.
Lateral?torsional coupling in asymmetric-plan buildings leads to correlated translations and rotations of the building plan, which generate uneven distributions of deformation demand among resisting planes. The deformation demand of a resisting plane depends on the relative magnitude of the plan translation and rotation and on the correlation between the two signals. Thus, small rotations highly correlated with building translation may lead to significantly different deformations of the resisting planes at the building edges. Consequently, the use of supplemental dampers is intended not only to reduce the magnitude of the plan translation and rotation, but also the correlation between these motions. For the sake of simplicity, linear viscous dampers are used in this investigation, which properly located in plan lead to a minimum response of the geometric center, thus achieving the same mean-square value of the displacements at the building edges. Mathematically, this condition may be understood as creating zero correlation between the translations and rotation at the geometric center of the plan, which represents an uncoupling in the mean-square sense. Results show that the optimal damper location depends on the static eccentricity and frequency ratio of the bare structure, the total amount of supplemental damping considered, and the frequency content of the excitation. Through a final 6-story model example, the torsional balance concept is demonstrated to work on multistory buildings subjected to bidirectional ground motions.
Keywords: Torsional balance; Plan asymmetry; Lateral?torsional correlation; Earthquake response